2019
DOI: 10.28947/hrmo.2019.20.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de actividad de la chachalaca pálida (Ortalis poliocephala)

Abstract: Los patrones de actividad de las poblaciones animales fluctúan a lo largo del año, como respuesta a la disponibilidad de recursos, cambios en el clima y actividad de depredadores. Estudiar los patrones de actividad de las especies es necesario no sólo para aumentar el conocimiento de su historia natural sino también para la planeación de muestreos acordes a los periodos de mayor actividad. Con la finalidad de reconocer los patrones de actividad de la chachalaca pálida (Ortalis poliocephala) en una selva seca d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Our results are in disagreement with previous studies employing video cameras for monitoring daily activity in other cracids, including Chachalacas, which found bimodal patterns in diurnal activity with peaks at sunrise and sunset and no nocturnal sightings (Srbek–Araujo et al, 2012; Lafleur et al, 2014; Lavariega et al, 2019; Senič, 2020). Further research should evaluate whether the nocturnal vocalizations and the unimodal pattern of vocal activity of the Chaco Chachalaca is a rare behavior among cracids or whether it is related to the employment of autonomous sound recorders for monitoring daily activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in disagreement with previous studies employing video cameras for monitoring daily activity in other cracids, including Chachalacas, which found bimodal patterns in diurnal activity with peaks at sunrise and sunset and no nocturnal sightings (Srbek–Araujo et al, 2012; Lafleur et al, 2014; Lavariega et al, 2019; Senič, 2020). Further research should evaluate whether the nocturnal vocalizations and the unimodal pattern of vocal activity of the Chaco Chachalaca is a rare behavior among cracids or whether it is related to the employment of autonomous sound recorders for monitoring daily activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The study of the activity patterns of cracids is important to understand their biology and contribute to their conservation and management strategies (Baldo & Mennill, 2011; Nunes, 2015; Lavariega et al, 2019). In this study, we identified the hours and months with higher vocal activity of Chaco Chachalaca that will be useful to save efforts of future monitoring programs aiming to study the species.…”
Section: Discussionmentioning
confidence: 99%